Calophyllaceae plastomes, their structure and insights in relationships within the clusioids - Trad, Rafaela Jorge; Cabral, Fernanda Nunes; Bittrich, Volker; Silva, Saura Rodrigues da [UNESP]; Amaral, Maria do Carmo Estanislau do (Springer Nature, 2021)
A complete chloroplast genome is not yet available for numerous species of plants. Among the groups that lack plastome information is the clusioid clade (Malpighiales), which includes five families: Bonnetiaceae, Calophyllaceae, Clusiaceae, Hypericaceae, and Podostemaceae. With around 2200 species, it has few published plastomes and most of them are from Podostemaceae. Here we assembled and compared six plastomes from members of the clusioids: five from Calophyllaceae (newly sequenced) and one from Clusiaceae. Putative regions for evolutionary studies were identified and the newly assembled chloroplasts were analyzed with other available chloroplasts for the group, focusing on Calophyllaceae. Our results mostly agree with recent studies which found a general conserved structure, except for the two Podostemaceae species that have a large inversion (trnK-UUU–rbcL) and lack one intron from ycf3. Within Calophyllaceae we observed a longer LSC and reduced IRs in Mahurea exstipulata, resulting in some genic rearrangement, and a short inversion (psbJ–psbE) in Kielmeyera coriacea. Phylogenetic analyses recovered the clusioids and the five families as monophyletic and revealed that conflicts in relationships reported in the literature for the group agree with nodes concentrating uninformative or conflicting gene trees. Our study brings new insights about clusioid plastome architecture and its evolution.